KOMPARASI KEHUJJAHAN HADITS DHA’IF PERSPEKTIF IMAM ABU HANIFAH DAN IMAM AHMAD BIN HANBAL - Khafifatul Fian; Munawir Munawir (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2023)
This study aims to explain the hadith dha'if by comparing the thoughts of Imam Abu Hanifah and Imam Ahmad bin Hanbal. The type of research used is a literature review through data collection techniques by tracing sources either from articles, books, or other sources relevant to the topic of discussion. After the data is collected, the researchers descriptively analyze and the next step is to conclude. The results showed that on the thought of Imam Abu Hanifah related to the hadith dha'if it is permissible to practice it for something related to the practice or law of sharia and with the provision that the level is not very weak and there are no other postulates that have conflicts with the hadith. Meanwhile, according to Imam Ahmad bin Hanbal, it is the same as his thought that Imam Abu Hanifah to allow for the use of hadith dha'if with provisions on discussions related to Practice but not something that discusses the law.